The use of bladder voiding efficiency in assessing benign prostatic enlargement - Philimon Kapesa; Kasonde Bowa (African Journal of Urology, 2022)
Abstract Background The management of benign prostatic enlargement (BPE) in low resource settings poses a major challenge in Africa. The objective of the study was to investigate the accuracy of Bladder Voiding Efficiency (BVE) to assess lower Urinary Tract Symptoms (LUTS) among BPE patients in a low resource setting. Methods From December 2017 to March 2018, patients with benign prostatic enlargement (BPE) and Lower Urinary Tract Symptoms (LUTS) were recruited into the study. The study was a prospective cross-sectional study. Participants had the International Prostate Symptom Score (IPSS) recorded followed by evaluation of their Bladder Voiding Efficiency (BVE). The BVE was calculated as the ratio of the volume of Urine voided over total volume of Urine in the bladder at the time of the void. The data were analysed to show the Sensitivity and Specificity of BVE in symptomatic LUTS. The Pearson correlation co-efficient between IPSS and BVE was analysed. Results The study recruited 94 participants. The age range was 45 to 85 year. The mean age was 68.1 years. The sensitivity of BVE to detect severe LUTS was 97.97%, while the specificity of BVE to detect mild to moderate disease was 97.78%. The correlation coefficient between IPSS and BVE was negatively correlated at 0.89, and this was statistically significant (P < 0.001). Conclusion The Bladder Voiding Efficiency (BVE) is a highly sensitive and specific test in our population to detect LUTS. It is well correlated to the International Prostate Severity Score in this study population.